2004
DOI: 10.1073/pnas.0404944101
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of long-range neural synchrony reflects temporal limitations of visual attention in humans

Abstract: Because of attentional limitations, the human visual system can process for awareness and response only a fraction of the input received. Lesion and functional imaging studies have identified frontal, temporal, and parietal areas as playing a major role in the attentional control of visual processing, but very little is known about how these areas interact to form a dynamic attentional network. We hypothesized that the network communicates by means of neural phase synchronization, and we used magnetoencephalog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
435
5
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 535 publications
(490 citation statements)
references
References 48 publications
45
435
5
5
Order By: Relevance
“…First, studies using functional imaging methods have suggested that target processing in the attentional blink task is mediated by a widespread cortical network including parietal cortex, anterior cingulate cortex, and lateral frontal cortex (Marois, Chun, & Gore, 2000) and that activation differences in these cortical areas correlate with T2 performance (Kranczioch, Debener, Schwarzbach, Goebel, & Engel, 2005;Marois, Yi, & Chun, 2004). Converging evidence for a relationship between activity in this network and T2 performance has been reported in a recent MEG study (Gross et al, 2004). It is interesting to note that the parietal and frontal cortex are the cortical areas with the densest noradrenergic innervation (Levitt, Rakic, & Goldman-Rakic, 1984;Morrison & Foote, 1986).…”
Section: Relationship With the P3 Neuroimaging Data And Neuropsychomentioning
confidence: 94%
“…First, studies using functional imaging methods have suggested that target processing in the attentional blink task is mediated by a widespread cortical network including parietal cortex, anterior cingulate cortex, and lateral frontal cortex (Marois, Chun, & Gore, 2000) and that activation differences in these cortical areas correlate with T2 performance (Kranczioch, Debener, Schwarzbach, Goebel, & Engel, 2005;Marois, Yi, & Chun, 2004). Converging evidence for a relationship between activity in this network and T2 performance has been reported in a recent MEG study (Gross et al, 2004). It is interesting to note that the parietal and frontal cortex are the cortical areas with the densest noradrenergic innervation (Levitt, Rakic, & Goldman-Rakic, 1984;Morrison & Foote, 1986).…”
Section: Relationship With the P3 Neuroimaging Data And Neuropsychomentioning
confidence: 94%
“…Hipp et al (2011) have identified large scale beta synchronization in a distinctive network of frontal, parietal and extrastriate visual areas in relation to visual perceptual organization. Fronto-parietal synchrony in the beta band also has been associated with visual search (Buschman and Miller, 2007), integration of visual information and perceptual grouping (Srinivasan et al, 1999;Phillips and Takeda, 2009;Phillips et al, 2012;Volberg and Greenlee, 2014;Castellano et al, 2014), visual attention (Gross et al, 2004;Marois et al, 2000;Wróbel, 2000), and visual object recognition (Sehatpour et al, 2008;Castellano et al, 2014). These previous studies, however, point to the existence of ongoing fronto-parietal beta synchronization that modulates brain responses to visual input (Gross et al, 2004;Liang et al 2002;Hipp et al, 2011), or beta synchrony at later stages (150-300 ms) of visual stimulus processing (Phillips et al, 2012;Sehatpour et al, 2008;Dehaene and Changeux, 2011).…”
Section: Fronto-parietal Beta Synchronization During Visual Processingmentioning
confidence: 98%
“…Interestingly, right parietal and left frontal regions were identified by Gross et al (2004) as critical for the functioning of a beta target-related network likely representing a state of increased sensitivity (higher vigilance). Exactly these pairs were pathologically enhanced in patients with right hemisphere lesion without neglect.…”
Section: Fronto-parietal Beta Synchronization During Visual Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant advantage of synchrony over coherence for the study of attentional phenomena is that by using wavelet analysis, synchrony can be calculated with higher temporal resolution than FFT methods that require several seconds or more of EEG data to calculate coherence. Using magneto-EEG to investigate the attentional blink phenomenon, neuronal synchrony in the beta band locations was increased during successful detection (non-blink) and decreased during missed letters (attentional blink) (Gross et al, 2004). Event-related covariance is another measure of relationship between different locations and decreases in event-related covariance have been related to performance decrements on sustained attention tasks (Gevins et al, 1987).…”
Section: Physiologic Correlatesmentioning
confidence: 99%